Tantangan Budaya dalam Mewujudkan Kesetaraan Gender di India dan Solusinya - Agneta Kristalia Tedjo; Mohammad Daffa Ramadhan; Muhammad Daffa Dirgantara; Raden Arief Meivio Bahari (Universitas Airlangga, 2021)
Gender equality has become a topic that people discuss about a lot over the last few years. A condition where women and men should have equal position on every aspect of life is indeed should be realized in everywhere part of the world, including India. Therefore, this article will discuss an overview of the condition of gender equality in India and how the situation of women there. India was named by the Tom Reuters Foundation as the 4th most dangerous country in the world. One of the many factors why this is happen because of the existence of cultural traditions that have deeply rooted for generations. Because of that, it is necessary to discuss further the importance of gender equality in India. It will be explained about the solution of the culture that have deeply rooted in India, especially the culture that bring harm to women. Education is one aspect that is used to reduce any discrimination that is exist in India. The main goal of India in education is to overcome high illiteracy rate and also educational inequality for women. It will also be discussed, what are the roles of outsiders involved in the realization of gender equality in India. How conventions such as the Convention on Elimination of the All Forms of Discrimination Against Women (CEDAW) also play a role in helping India achieve gender equality and fulfillment of human rights, especially for women. . As well as how the role of the Indian government to create a good environment for women.